2014
DOI: 10.1007/s12603-013-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine in tea Camellia sinensis — Content, absorption, benefits and risks of consumption

Abstract: Therapeutic properties of tea Camellia sinensis are of particular interest since it has been consumed for ages and was always regarded as safe beverage. Tea is most popular beverage in the world because of its attractive aroma, exceptional taste, health promoting and pharmaceutical potential. Current results showed that antioxidative, antibacterial and other health effects are attributed to its caffeine content and caffeine - polyphenols interactions. An overview is given on caffeine content in different tea l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 88 publications
0
30
0
Order By: Relevance
“…We found that high-frequency tea intake was also significantly associated with rosacea occurrence other than aggravation in the present study for the first time. 33 Studies reported that caffeine played a significant role in sleep deprivation and activation of sympathetic nerves, 34 mediating skin vasodilatation through stimulating iontophoresis of acetylcholine. However, it is not always made at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that high-frequency tea intake was also significantly associated with rosacea occurrence other than aggravation in the present study for the first time. 33 Studies reported that caffeine played a significant role in sleep deprivation and activation of sympathetic nerves, 34 mediating skin vasodilatation through stimulating iontophoresis of acetylcholine. However, it is not always made at high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, the amount of caffeine in most teas is more than that in coffee. 33 Studies reported that caffeine played a significant role in sleep deprivation and activation of sympathetic nerves, 34 mediating skin vasodilatation through stimulating iontophoresis of acetylcholine. 35 Increased sympathetic excitability and vasodilatation were thought to be involved in the occurrence and development of flushing and subcutaneous telangiectasia in rosacea.…”
Section: Discussionmentioning
confidence: 99%
“…No association was found with TDP, analogously to what was observed in our previous InCHIANTI studies regarding all-cause mortality (17), substantial cognitive decline (34), and frailty syndrome (35). These differences in the results between TUP and TDP could be due to bioavailability and interactions of polyphenols with other compounds, such as caffeine (36). Thus, TUP measurement takes into account polyphenol bioavailability that highly varies between and within subjects (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also in tea other substances different from caffeine might also affect cognition in man, such as theanine that crosses the BBB and is present in tea and mushroom (40,101). Polyphenols, particularly flavonoids like catechins (flavan-3-ols), constitute the most interesting group of green tea leaf components (102,103). Green tea contains more catechins than black tea or oolong tea, and these substances are in vitro and in vivo strong antioxidants.…”
Section: The Journal Of Nutrition Health and Aging© J Nutr Health Agingmentioning
confidence: 99%